Teaching Product Design Through The CANVA Application To Enhance The Brand Image Of The Company - Orisa, Mira; Faisol, Ahmad; Ashari, Muhammad Ibrahin (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The study aims to investigate the effectiveness of using Canva applications to improve employees' graphic design skills. The research was conducted by observing a company that operates in the areas of Maintenance service, General supply and renovation. This research activity is designed into several stages such as the partner observation phase, the preparatory stage of training, the training stage, and the final stage of evaluation. Based on observations stated that the company has employees from various disciplines such as electro, civil, electric energy. We provide training to employees in graphic design. For us this knowledge is also very important to the employees to help companies improve their brand image. In the business world, one of the most crucial marketing tools for presenting and promoting a product to potential customer is an engaging and educational product design presentation. The purpose of this study is to determine how simple it is to create brand image successful like a poster, flyers, logo, and brochure using Canva's graphic design platform. Users can easily design and edit with Canva's array of design tools, which include text tools, color adjustment tools, image manipulation tools, grid tools, and more. They can design their brand image easily using online applications like canva. canva provides easy access anywhere and anytime because it is internet-based.